2020
DOI: 10.1063/5.0002251
|View full text |Cite
|
Sign up to set email alerts
|

Synchronization in reaction–diffusion systems with multiple pacemakers

Abstract: Spatially extended oscillatory systems can be entrained by pacemakers, regions which oscillate with a higher frequency than the rest of the medium. Entrainment happens through waves originating at a pacemaker. Typically, biological and chemical media can contain multiple pacemaker regions which compete with each other. In this paper we perform a detailed numerical analysis of how wave propagation and synchronization of the medium depend on the properties of these pacemakers. We discuss the influence of the siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
2
5
0
Order By: Relevance
“…In the latter case, the wave direction reverses, as the local concentration in the center is increased, leading to a higher cell cycle frequency. These observations are in agreement with an earlier theoretical analysis of competing pacemakers [37].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the latter case, the wave direction reverses, as the local concentration in the center is increased, leading to a higher cell cycle frequency. These observations are in agreement with an earlier theoretical analysis of competing pacemakers [37].…”
Section: Discussionsupporting
confidence: 93%
“…Moreover, in 2d, there is much more freedom to explore different sizes and geometries of pacemakers (e.g. nuclei), which in 1d has shown to be of importance for the dynamics of the system [37].…”
Section: B Future Workmentioning
confidence: 99%
“…In the latter case, the wave direction reverses, as the local concentration in the center is increased, leading to a higher cell cycle frequency. These observations are in agreement with an earlier theoretical analysis of competing pacemakers [25].…”
Section: A Waves In Import-reaction-diffusion Systemssupporting
confidence: 93%
“…When this is the case, they compete with each other until one takes over the whole medium. We recently investigated such systems of multiple pacemakers [52] and showed that both size and frequency matter in the determination of which pacemaker dominates the whole medium.…”
Section: Discussionmentioning
confidence: 99%